Synchronous esophagus and pancreas tumor - Santandreu, Jorge; Nogués, Cecile; Moure, Luis; Rodríguez, Julio (Cirugía del Uruguay, 1996)
The present report deals with a clínica/ picture marked by an unusua/ synchronic neoplasic association at the digestive, esophague and pancreatic leve/.